TRAINING FUTURE PSYCHOLOGISTS TO APPLY COACHING STRATEGIES IN COUNSELING CLIENTS - Viktoriia Bykova; Hanna Voshkolup; Iryna Oliinyk (Alfred Nobel University Journal of Pedagogy and Psychology)
The growing demand for resource-oriented and client-centred approaches in psychological practice necessitates updating the professional training of specialists. The authors analyse the essence of coaching as a modern direction of psychological assistance based on the principles of partnership, support, aware- ness, and goal orientation. The purpose of this work is to theoretically substantiate and define the main approaches to train- ing future psychologists to apply coaching strategies in the process of psychological counselling, as well as to outline effective forms, methods and conditions for integrating coaching technologies into professional training. The objectives of this scientific research are to analyse the essence of the concept of “coaching” and determine its place in the system of psychological counselling, to identify effective forms, methods and means of implementing coaching strategies in the process of professional training of psychologists, to sub- stantiate the directions of improving the educational process in order to form the readiness of future psy- chologists to use coaching in counselling clients. The study employs methods of theoretical analysis of scholarly literature, comparative analysis, sys- tematisation and generalisation of scientific approaches to the interpretation and conceptualisation of coaching technologies in psychological counselling, as well as modelling and designing an academic course aimed at preparing prospective psychologists to apply coaching strategies in professional counselling prac- tice. The importance of training future psychologists to apply coaching strategies in their professional activities is emphasized. The main aspects of the integration of the coaching approach into psychologi- cal counselling are determined, the need to develop relevant skills in future psychologists is substantiated. The modern scientific approaches to the definition of the concept of “coaching” are analysed, its po- tential in the context of psychological counselling is revealed. It has been established that coaching is a pro- cess through which a specialist helps to unlock an individual’s inner potential and activate their motivation- al system, aiming to achieve goals in various areas of life as effectively as possible. Coaching strategies in psychological counselling are focused on individual work with a client who seeks to improve their life in any given context. As a result of the study, the directions of improvement of the educational process in order to form the readiness of future psychologists to use coaching strategies in their professional activities are outlined. Em- phasis is placed on the importance of practice-oriented training of psychology students, including interac- tive forms of training, modelling of counselling situations, use of coaching methods, tools and strategies. The main methods and technologies of coaching used in the counselling process are described, with their practical application implemented within the framework of the course “Fundamentals of Psychological Counselling” for undergraduate students of the 053 Psychology specialty, enrolled in the educational and professional programme “Counselling and Corrective-Developmental Work”. It has been concluded that effective training of future psychologists for the application of coaching strategies in the process of counselling requires an integrated approach that combines theoretical validity, practical orientation, development of professionally important qualities and skills, as well as the creation of a motivational environment for personal and professional growth.